Low prevalence of H. pylori Infection in HIV-Positive Patients in the Northeast of Brazil - Silva Cícero IS; Takeda Christianne FV; Sun Juliana LM; Fernandes Karine C; Fialho André MN; Guerra Eder JC; Braga-Neto Manuel B; Fialho Andréa BC; Queiroz Dulciene MM; Braga Lucia LBC (BMC Gastroenterology, 2011)
Abstract Background This study conducted in Northeastern Brazil, evaluated the prevalence of H. pylori infection and the presence of gastritis in HIV-infected patients. Methods There were included 113 HIV-positive and 141 age-matched HIV-negative patients, who underwent upper gastrointestinal endoscopy for dyspeptic symptoms. H. pylori status was evaluated by urease test and histology. Results The prevalence of H. pylori infection was significantly lower (p < 0.001) in HIV-infected (37.2%) than in uninfected (75.2%) patients. There were no significant differences between H. pylori status and gender, age, HIV viral load, antiretroviral therapy and the use of antibiotics. A lower prevalence of H. pylori was observed among patients with T CD4 cell count below 200/mm3; however, it was not significant. Chronic active antral gastritis was observed in 87.6% of the HIV-infected patients and in 780.4% of the control group (p = 0.11). H. pylori infection was significantly associated with chronic active gastritis in the antrum in both groups, but it was not associated with corpus chronic active gastritis in the HIV-infected patients. Conclusion We demonstrated that the prevalence of H. pylori was significantly lower in HIV-positive patients compared with HIV-negative ones. However, corpus gastritis was frequently observed in the HIV-positive patients, pointing to different mechanisms than H. pylori infection in the genesis of the lesion.